2024
DOI: 10.5009/gnl240023
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Functional Cure for Hepatitis B

Anna S. F. Lok

Abstract: Current treatment of chronic hepatitis B virus (HBV) infection, pegylated interferon-α (pegIFN-α) and nucleos(t)ide analogue (NA), can suppress HBV replication, reverse liver inflammation and fibrosis, and decrease risks of cirrhosis and hepatocellular carcinoma, but hepatitis B surface antigen (HBsAg) loss is rare. Functional HBV cure is defined as undetectable HBsAg and unquantifiable serum HBV DNA for at least 24 weeks after a finite course of therapy. This requires suppression of HBV replication and viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…As a result, a diverse array of investigational drugs is presently in development and undergoing clinical trials, including direct-acting antivirals such as entry inhibitors, RNA interference agents (small interfering RNA [siRNA] or antisense oligonucleotides), HBsAg release inhibitors, capsid assembly modulators (CAMs) -also known as core protein inhibitors -and immune modulators. 1 Among these agents, core protein inhibitors emerge as promising drugs due to the pivotal role of the core protein in HBV persistence across various stages of the viral cycle. There are two types of core protein inhibitors: Type 1, involved in aberrant capsid formation, and Type 2, responsible for generating an empty capsid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a diverse array of investigational drugs is presently in development and undergoing clinical trials, including direct-acting antivirals such as entry inhibitors, RNA interference agents (small interfering RNA [siRNA] or antisense oligonucleotides), HBsAg release inhibitors, capsid assembly modulators (CAMs) -also known as core protein inhibitors -and immune modulators. 1 Among these agents, core protein inhibitors emerge as promising drugs due to the pivotal role of the core protein in HBV persistence across various stages of the viral cycle. There are two types of core protein inhibitors: Type 1, involved in aberrant capsid formation, and Type 2, responsible for generating an empty capsid.…”
mentioning
confidence: 99%
“…10 Studies have demonstrated that adding a core protein inhibitor to NUCs leads to a more potent reduction in viral activity compared to NUCs alone, 11,12 and HBsAg seroclearance has been observed with the combination of a core protein inhibitor with siRNA and pegIFN-α. 1 Considering that many current CHB patients are already undergoing NUCs treatment, the efficacy of sequential therapy, as one modality for combining different approaches, with the newer agents is also expected.…”
mentioning
confidence: 99%